Cell proliferation monitoring by multiplexed electrochemical impedance spectroscopy on microwell assays. Issue 5 (9th April 2013) - Duchateau, Stijn; Broeders, Jeroen; Croux, Dieter; Janssen, Daniel; Rigo, Jean‐Michel; Wagner, Patrick; Thoelen, Ronald; De Ceuninck, Ward; Krishna, Sanjay; Plis, Elena
Abstract Cell proliferation can be monitored by a wide range of well‐established techniques. Most of the principles used rely on optical, single end‐point methods, often involving the use of absorbent, fluorescent or luminescent compounds. These additives can interfere with the cell growth, thus producing distorted results. Electrochemical impedance spectroscopy provides a solution for this problem and enables continuous monitoring without interference. However equipment for this measurement technique is often bulky, highly expensive and lacks multichannel features. This paper presents a low‐cost, compact hardware platform optimized for proliferation measurements, together with custom software to ease interpretation and physical modelling of data. Performance is demonstrated and measurement parameters are fine‐tuned for three commonly used cell types in proliferation measurements. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)